VIOLENCE AGAINST HEALTH WORKERS AND MEASURES TO PREVENT VIOLENCE - Çiğdem Müge HAYLI (Rojan GÜMÜŞ, 2020)
Violence in Health, which constitutes a serious problem in Turkey and all over the world has become a global problem. It is admirable by every segment that healthcare professionals today struggle with a global problem such as covit-19 virus or serve altruistically in every period. Nevertheless, while providing services, they somehow experience communication problems with their patients and relatives, and they are subjected to physical, verbal or psychological violence. In order to prevent violence for employees who are exposed to violence for many reasons; Work should be done on issues such as security, physical structure and equipment, communication, education, and making necessary revisions in the legal regulations on this subject motivates healthcare professionals. Health violence is not only caused by healthcare professionals, patients or their relatives. The working system of the institutions, the patient density is high, the health personnel are insufficient, the social and global factors, as well as the news in the media that we pay particular attention to in our study, can lead to the emergence of violence. The existence of violence in social life is a result of mass media's inevitably publishing the violence in health. This is why the positive developments and negative events in the field of health are published in the media. The purpose of our study is to prepare a stress-free, worry-free working environment for our future healthcare professionals and us without understanding our colleagues.